Preliminary evidence on the use of telehealth in an outpatient behavior clinic. Issue 3 (22nd March 2016) - Suess, Alyssa N.; Wacker, David P.; Schwartz, Jessica E.; Lustig, Nicole; Detrick, Jessica
Abstract : Previous studies have shown that telehealth can be an effective way to deliver behavior‐analytic services. In this study, we provided a demonstration of the use of telehealth to assess and initiate treatment of problem behavior in an outpatient clinic. We coached parents of children with autism via telehealth to conduct functional analyses during 1 appointment that lasted 1 hr and subsequently coached them as they implemented functional communication training during 3 subsequent appointments (15 min each). Social functions were identified for most children, and problem behavior was reduced by an average of 65.1%.